A new species of Plaumanniola Costa Lima in French Guiana (Coleoptera: Staphylinidae) - Jałoszyński, Paweł (Zootaxa, 2018)
The genus Plaumanniola Costa Lima, 1962 was a subject of several taxonomical and morphological studies. It is one of very few scydmaenines originally placed not only in a different beetle family, but even a superfamily. The first species of Plaumanniola, P. sanctaecatharinae Costa Lima, 1962 was confused with myrmecophilous spider beetles and placed in a new subfamily Plaumanniolinae of Ptinidae. Transferred to Scydmaenidae by Lawrence & Reichardt (1966), it remained placed as a separate subfamily, and after merging the ant-like stone beetles with Staphylinidae, as a tribe Plaumanniolini of Scydmaenitae (Newton & Franz 1998; Grebennikov & Newton 2009). Franz (1990) redescribed P. sanctaecatharinae, but Jałoszyński (2013) found his redescription to have been based on a misidentified new species, which he described as P. regina Jałoszyński, 2013. The latter author illustrated previously unknown morphological structures, redefined Plaumanniola and discussed its possible close affinities with Glandulariini (Jałoszyński 2013). The unusually stout and flattened body, with especially flat and broad head (interpreted as possible adaptations towards myrmecophily, e.g., Lenko (1972)), differentiated Plaumanniolini from all other Scydmaeninae, but no other characters were found to support a separate position of this monogeneric tribe. Shortly later, a relatively slender P. simplicissima Jałoszyński, 2014 was described on the basis of material collected in Bolivia. Finally, a discovery made by Jałoszyński (2016) that Euconnus octosetosus Franz, 1994, was in fact a strikingly slender member of Plaumanniola, and that the aedeagus of Plaumanniola highly resembles that of Euconnus (Rhomboconnus Franz, 1986), lead to placing Plaumanniolini as a junior synonym of Glandulariini. It is possible that in future Plaumanniola will be reduced to a subgenus of Euconnus.